Study on Influence of Electrodes in Electric Discharge Machining - Thanigaivelan, Rajasekaran; Arunachalam, Ramanathan; Natarajan, Nagamanaicker (Recent Patents on Mechanical Engineering, 2015)
Electric Discharge Machining (EDM) is a prominent machining technique used mainly to machine difficult to cut metals and alloys. The major challenges faced in EDM are high Tool Wear Rate (TWR), overcut and poor surface quality. To overcome these challenges, this research aims to improve the TWR and overcut. The experiments were conducted on the EDM using Copper (Cu) electrode, Cryogenically Treated (CT) Cu electrode, Brass electrode and CT Brass electrode by changing the voltage, pulse on-time and discharge current values. Based on the conducted experiments CT Cu electrode, there is a significant improvement in TWR and overcut by 24 times and 2.5 times respectively compared to other electrodes. Further, the incidence of micro-cracks and void occurring in workpiece due to heating and cooling on the cutting surface is analysed through SEM analysis which substantiates that the CT tool produces the least number of cracks compared to other electrodes. Patents related to electrodes, issued since 1994 are selected for the survey. On comparing these patents, it is evident that the most of the patents aim to minimize the tool wear through various mechanisms.
Keywords: EDM